UAV Tunnel Formation Based on Bearing-only Passive Location Optimization Algorithm - Peng, Pengming; Huang, Gang (Journal of physics. Conference series, 2023)
In the actual bearing-only passive UAV positioning system, both the controller and receiver are in non-standard positions. Three-point positioning cannot be carried out simply by a geometric algorithm. This study introduces positioning only by bearing-only information transmission without considering increasing the complexity of system sensors. When the circular formation and conical formation of UAVs are in abnormal positions to locate the unit and adjust it to the standard position, the error distance between the original position and its accurate position is taken as the target, and an iterative optimization model is established. The positions of other UAVs are revised according to the transmitter position information. Finally, the ideal error position information is obtained, which is regarded as the adjustment of the whole unit distance to the standard distance.